Elastisitas Harga Susu Sapi terhadap Jumlah Permintaan Bahan Baku Yoghurt pada Perusahaan Anisa Yoghurt (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines the price elasticity of fresh cow’s milk on the demand for raw materials at Anisa Yoghurt Company using a demand theory approach. Milk is the main input in yoghurt production, making price fluctuations potentially influential on production decisions. The objective of this research is to analyze the responsiveness of raw milk demand to price changes and to identify the elasticity characteristics of milk demand in a small-scale food processing business. This study employs a quantitative case study method using primary data collected through weekly observations of milk prices and quantities purchased over a three-month period, from September to November. The analysis applies the midpoint elasticity formula to measure price elasticity of demand. The findings indicate that the demand for raw milk is consistently inelastic across the observed periods, as shown by elasticity values with absolute magnitudes less than one. Both price decreases and increases result in relatively small changes in the quantity demanded, indicating low sensitivity of demand to price fluctuations. These results suggest that raw milk is an essential production input, and purchasing decisions are driven more by production needs than by short-term price changes. The study implies that yoghurt producers should prioritize supply stability and production efficiency rather than adjusting purchase volumes in response to minor price changes. This research contributes empirical evidence on demand elasticity in dairy-based agro-industries, particularly at the small enterprise level.